'You are not alone' - The role of social relationships in engagement in care for adolescents living with perinatally acquired HIV in Western Kenya - Taren L. McGray; Ken Ondeng'e; Gaëlle Sabben; Emma Clevenger; Richard Lando; Calvin Mbeda; Valarie Opollo; Kate Winskell (Elsevier, 2023)
This manuscript examines how social relationships influence engagement in care of adolescents with perinatally acquired HIV (APHIV) in Western Kenya, with the aim of informing efforts to improve APHIV outcomes. Interview and focus group transcripts with APHIV, caregivers, and healthcare providers from 2019 to 2021 were thematically analyzed through the lens of Bronfenbrenner's Socio-Ecological Model. Overall, caring relationships can improve APHIV engagement in care, often through the intermediary of mental health, via direct interactions and the social contexts these relationships create. Conversely, a lack of positive relationships diminishes APHIV's desire to live, leading to disengagement. Microsystem influences, such as adherence follow-up, are most influential because they help APHIV feel loved, normal, and less alone. Meso- and exosystem factors, including visiting relatives, support groups, and caregiver communication with others, create enabling or prohibitive environments for APHIV engagement. Macrosystem challenges related to stigma pervade each level, influencing APHIV's personal care management strategies and how individuals treat APHIV. Interventions focusing on strategies that strengthen the support perceived and received by APHIV from friends/peers, teachers, caregivers, and family can improve motivation for engagement in care. This may include improving counseling, training, and education for APHIV and those around them to mitigate engagement in care barriers, such as peer pressure, stigma, and disclosure-related challenges.